The middle way : the emergence of modern religious trends in nineteenth-century Judaism : responses to modernity in the philosophy of Z.H. Chajes, S.R. Hirsch and S.D. Luzzatto. - Chamiel, Ephraim (Studies in Orthodox Judaism., 2014)
This book in two volumes is devoted to examining the first encounter between traditional Judaism and modern European culture, and the first thinkers who sought to combine the Torah with science, revelation with reason, prophecy with philosophy, Jewish ethics with European culture, worldliness with sanctity, and universalism with the particular redemption of the Jews. These religious thinkers of the nineteenth century struggled with challenges of the modern age that continue to confront the modern Jews to this day. This objective work of scholarship, neither simplistic and isolationist nor destructive and arrogant, will be of interest to the modern thinker and to scholars of the history of religions. It is relevant to comparative study between Judaism and the various denominations of Christianity and other faiths that seek to find a middle way between their traditions and modernity.